Groundbreaking 3D printing technology for metal. (Research'eu results magazine)
Tapping the market for small, customised metal parts could boost the competitive position of 'Small and medium-sized enterprises' (SMEs). A new manufacturing platform enables mass production of 3D metal printed parts, and can also simultaneously clean and polish up to 100 parts in a single session.